2016
DOI: 10.1007/s12257-016-0405-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved cordycepin production in a liquid surface culture of Cordyceps militaris isolated from wild strain

Abstract: A Cordyceps militaris NBRC 10352-3 strain that was isolated from C. militaris NBRC10352 produced 68 mg of cordycepin from 100 ml of medium, which was the highest level of cordycepin among 60 isolates from three C. militaris (NBRC 9787, 100741 and 103752) strains. Interestingly, a liquid surface culture of C. militaris NBRC 103752-3 produced 2-fold cordycepin to that in a submerged culture. Cordycepin production was significantly affected by specific surface area (SSA) in the liquid surface culture, and 120.9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The consumption of phenylalanine suggested that it could be a candidate of additives to enhance the production of cordycepin. However, in our previous study, the addition of phenylalanine did not have any effect on cordycepin production in C. militaris (Sari, Suparmin, Kato, & Park, ).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The consumption of phenylalanine suggested that it could be a candidate of additives to enhance the production of cordycepin. However, in our previous study, the addition of phenylalanine did not have any effect on cordycepin production in C. militaris (Sari, Suparmin, Kato, & Park, ).…”
Section: Resultsmentioning
confidence: 61%
“…This fungus was inoculated into an optimized culture medium (Sari et al, ) composed of 72.5 g/L yeast extract, 62.6 g/L glucose (pH 5.6) and Vogel's medium with 1/10 concentration containing 0.28 g/L sodium citrate dihydrate, 0.50 g/L KH 2 PO 4 , 0.20 g/L NH 4 NO 3 , 0.02 g/L MgSO 4 ·H 2 O, 0.01 g/L CaCl 2 2H 2 O, 0.46 × 10 −3 g/L citric acid, 0.50 × 10 −3 g/L ZnSO 4 , 0.1 × 10 −3 g/L Fe(NH) 4 (SO 4 ) 2 .6H 2 O, and 0.025 × 10 −3 g/L CuSO 4 5H 2 O and incubated at 25°C for 19 days in liquid surface culture.…”
Section: Methodsmentioning
confidence: 99%
“…C . militaris was cultivated in an optimized production medium [ 15 ] composed of 72.5 g/L yeast extract, 62.6 g/L glucose (pH 5.6) and Vogel’s medium with 1/10 concentration containing 0.28 g/L sodium citrate dihydrate, 0.50 g/L KH 2 PO 4 , 0.20 g/L NH 4 NO 3 , 0.02 g/L MgSO 4 ·H 2 O, 0.01 g/L CaCl 2 ·2H 2 O, 0.46 × 10 −3 g/L citric acid, 0.50 × 10 −3 g/L ZnSO 4 , 0.1 × 10 −3 g/L Fe(NH) 4 (SO 4 ) 2 ·6H 2 O, and 0.025 × 10 −3 g/L CuSO 4 ·5H 2 O. One disk (1 cm diameter) of mycelia in PDA plates that had been cultured for 7 d was inoculated into 100 ml of the optimized production medium in a 500 ml Erlenmeyer flask and incubated at 25°C for 19 d in the LSC.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, cordycepin shows insecticidal activity to Plutella xylostella (Lepidoptera: Plutellidae) and Trypanosoma evansi [ 9 , 10 ]. Large amounts of cordycepin are produced in medium from surface cultures of mycelia [ 11 , 12 ]. This culture method supports large-scale production using mycelial cultivation instead of the preparation of fruiting bodies.…”
Section: Introductionmentioning
confidence: 99%